The art and archaeology of Venetian ships and boats - Martin, Lillian Ray. (London : Chatham Pub., 2001)
"Nautical archaeologist Lillian Ray Martin has collected representations of ships and boats in medieval and early Renaissance art. To do so, Martin systematically surveyed the museums, churches, libraries, and public buildings of Venice and the surrounding region in search of watercraft depicted in art." "Drawing on material from several disciplines, The Art and Archaeology of Venetian Ships and Boats combines discussions of art and history with scientific scholarship.".
"Excavations in the region so for have revealed only a few small boats, two merchant ships, and a galley, a limited sample of the ships and boats of Venetia, but offering the base on which to build. Archaeological, documentary, and iconographic evidence are here combined to paint a more accurate picture of Venetian watercraft."--BOOK JACKET.
Includes bibliographical references (p. [223]-226) and index.
Keywords: Ships in art; Art, Italian -- Italy -- Venice; Art, Medieval -- Italy -- Venice; Art, Early Renaissance -- Italy -- Venice; Navigation -- Italy -- Venice -- History; Venice (Italy) -- History -- 697-1508.